Integrating GIS and celular automata spatial model in evaluating urban growth : prospects and challenges - Samat, Narimah (2007)
Malaysia is experiencing rapid urban growth resulted from industrialization and economic policies adopted since 1970s. According to current planning policies and related growth projection, this process is expected to continue at least until the 2020 where Malaysia is planned to be a developed nation. Future urban growth requires a cohesive planning policy in order to ensure this growth does not have negative consequences to economy, environment and society that are experiencing land use transformations. Many studies have shown that an integration of GIS and cellular automata approach is suitable in modelling urban development; however, most of those studies are undertaken in western developed nations which have adequate planners and funds to manage modest population growth. In the context of developing nations like Malaysia, a locally-devised planning and management approach needs to be developed to plan, monitor, and control urban development in order to meet local challenges. This paper evaluates the prospects and challenges of using a GIS-based cellular automata model in planning and monitoring urban spatial growth in Malaysia.